I-CReST 2022 International Conference on Research and Practices in Science, Technology and Social Sciences - UiTM, Pusat Asasi (Pusat Asasi, UiTM Cawangan Dengkil, 2022)
The International Conference on Research and Practices in Science, Technology and Social Sciences (I-CReST) is an annual event organised by the Centre of Foundation Studies, Universiti Teknologi MARA (UiTM), Malaysia. With this year’s theme, “Transcending boundaries and sustaining livelihood through multidisciplinary research”, it aims to provide a constructive virtual avenue for researchers and scholars across the globe to network with each other via the presentation of their impactful research works. In response to the spread of COVID-19 and its devastating effects, the conference focuses on providing a platform for the dissemination of research findings and intellectual discussions on diverse topics relating to sustaining livelihood. This conference has a typical format of 20-40 minutes of sharings or presentations by plenary and keynote speakers, as well as invited presenters, who are experts in their respective fields. The slots are subsequently followed by the Q&A or discussion session. This conference has also made it possible for more presentations in the form of prerecorded videos that are streamed via YouTube, thus promoting more academic engagement. Since its inaugural event in 2020, I-CReST has received tremendous positive responses from participants of various educational and industrial backgrounds. I-CReST 2022 garnered around 180 abstracts on cutting-edge topics within the scopes of science, technology and social sciences, as well as those of cross-disciplinary nature. The conference also provides opportunities for publication in proceedings with e-ISBN. Selected papers will be considered for publication in journals indexed by WOS/Scopus/MyCite/MyJournal after a thorough peer- reviewed process.